Dynamical Analysis of Mpox Transmission Model Incorporating Asymptomatic Individuals - Tuhfatul Janan; Fatmawati; Agus Hasan (The Indonesian Bio-Mathematical Society, 2026)
In this paper, we develop a mathematical model for the transmission dynamics of monkeypox (Mpox) involving both human and rodent populations, with the human population including asymptomatic individuals. The analysis begins by establishing the well-posedness of the model using the contraction mapping principle, ensuring the existence, uniqueness, and stability of the solution. The model is further examined for the boundedness and non-negativity of the solutions. Three equilibrium points are identified: the disease-free equilibrium, the human-endemic equilibrium, and the endemic equilibrium. The disease-free equilibrium is shown to be both locally and globally asymptotically stable when the basic reproduction number is less than one. If they exist, the human-endemic equilibrium is proven to be globally asymptotically stable when the basic reproduction number of the rodent population is less than one, and the endemic equilibrium is always globally asymptotically stable. The sensitivity analysis indicates that vaccination and contact dynamics are the most influential factors in human transmission, while rodent transmission is primarily shaped by contact rates and mortality-related factors. Numerical simulations are provided to illustrate and validate the analytical results.